Instructional Leadership Practices and their Influence on Curriculum Implementation in Basic Education (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined instructional leadership practices of school leaders and their influence on curriculum implementation in secondary basic education. Anchored in the premise that school leadership effectiveness is central to improving teaching and learning outcomes, this analysis examines how principals and school heads exercise instructional supervision, set academic goals, support teacher professional development, and foster a conducive learning environment. Using a mixed-methods design, the study gathered qualitative data from interviews with school leaders (4) and quantitative survey responses from teachers (64) to examine leadership practices and curriculum delivery alignment. Findings indicate that strong instructional leadership significantly enhances curriculum implementation when leaders actively engage in classroom observations, provide constructive feedback, and promote collaborative professional learning among teachers. The area of research is instructional leadership and curriculum implementation in secondary basic education. Findings indicate that a strong, positive, and statistically significant relationship exists between instructional leadership and effective curriculum implementation when leaders actively engage in classroom observations, provide constructive feedback, and promote collaborative professional learning among teachers. Effective school leadership also strengthens alignment between curriculum standards and classroom practices, improving instructional quality and learner outcomes in secondary basic education. The study's outputs are empirical evidence that proactive instructional leadership marked by regular classroom observation, constructive feedback, and collaborative professional learning has a positive, statistically significant effect on curriculum implementation in secondary basic education, and a set of practical recommendations for school leaders to protect instructional time